AN ERROR ANALYSIS OF ENGLISH RECOUNT TEXTS WRITTEN BY INDONESIAN SENIOR HIGH SCHOOL STUDENTS - Anakampun, Rizky Ananda; Fithriani, Rahmah (Universitas Islam Sumatera Utara (UISU), 2023)
Error analysis is widely used in EFL teaching and learning to identify the types and causes of errors made by EFL learners and to determine whether those errors are systematic or random. By examining these errors, teachers can develop effective solutions to reduce, eliminate or improve them. The purpose of this study was to investigate the grammatical errors made by senior high school students when composing recount texts. The study used a descriptive quantitative approach by analysing a corpus of 30 essays written by 15 students. Utilizing Dulay, Burt, Krashen's (1982) framework of surface structure taxonomy for data analysis, the results reveal that students committed errors in four categories: disinformation, misordering, omission, and addition (ordered accordingly from the most to the least produced one). This study implies that recognizing students' writing errors may assist teachers in determining the focus of their instruction in order to enhance student’s learning to a better condition.